복강경 충수절제술로 치료한 급성 충수염의 항생제 감수성 및 세균학적 고찰 - 이재원(Jae-Won Lee); 박중민(Joong-Min Park); 이승은(Seung-Eun Lee); 박용검(Yong-Geum Park); 지경천(Kyong-Choun Chi) (Annals of surgical treatment and research, 2010)
Purpose: This study was designed to evaluate the bacteriological characteristics and antibiotics sensitivity in acute appendicitis. Methods: The microbiologic culture and antibiotics sensitivity tests were done on 165 patients who underwent laparoscopic appendectomy under the diagnosis of acute appendicitis. The postoperative complications were also checked. The microbiologic and clinical results were compared between perforated and non-perforated groups. Results: The most common organism cultured from the periappendiceal fluid was Escherichia coli (51.2%), followed by Enterobacter (16.2%) and Pseudomonas (8.9%). In the antibiotics sensitivity test, ciprofloxacin and levofloxacin were highly susceptible. Ceftriaxone and cefotaxime were also highly susceptible. Piperacillin/tazobactam, imipenem and meropenem were very highly susceptible. The complication rate of perforated appendicitis group (17.9%) was higher than that of the non-perforated appendicitis group (7.1%) (P＜0.001). A surgical drain was used more frequently in perforated group (23% vs 84.6%, P＜0.001). The mean in-patient days were longer in the perforated group (5.7 vs 7.2 days, P＜0.001). In the patients with infectious wound complication, antibiotic resistance was more prominent in the non-perforated group than in the perforated group. Conclusion: In the perforated appendicitis group, more precise and careful procedure was required. In the non-perforated appendicitis group, more prudent use of the available antibiotics to conserve valuable therapeutic resources and improved infection control to limit the spread of resistant organisms was required. Purpose: This study was designed to evaluate the bacteriological characteristics and antibiotics sensitivity in acute appendicitis. Methods: The microbiologic culture and antibiotics sensitivity tests were done on 165 patients who underwent laparoscopic appendectomy under the diagnosis of acute appendicitis. The postoperative complications were also checked. The microbiologic and clinical results were compared between perforated and non-perforated groups. Results: The most common organism cultured from the periappendiceal fluid was Escherichia coli (51.2%), followed by Enterobacter (16.2%) and Pseudomonas (8.9%). In the antibiotics sensitivity test, ciprofloxacin and levofloxacin were highly susceptible. Ceftriaxone and cefotaxime were also highly susceptible. Piperacillin/tazobactam, imipenem and meropenem were very highly susceptible. The complication rate of perforated appendicitis group (17.9%) was higher than that of the non-perforated appendicitis group (7.1%) (P＜0.001). A surgical drain was used more frequently in perforated group (23% vs 84.6%, P＜0.001). The mean in-patient days were longer in the perforated group (5.7 vs 7.2 days, P＜0.001). In the patients with infectious wound complication, antibiotic resistance was more prominent in the non-perforated group than in the perforated group. Conclusion: In the perforated appendicitis group, more precise and careful procedure was required. In the non-perforated appendicitis group, more prudent use of the available antibiotics to conserve valuable therapeutic resources and improved infection control to limit the spread of resistant organisms was required. KCI Citation Count: 2